2016
DOI: 10.14319/ijcto.41.5
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning and cross-comparison of four scanning water tanks

Abstract: Purpose: Water scanning systems are commonly used for data collection to characterize dosimetric properties of photon and electron beams, and the commissioning of such systems has been previously described. The aim in this study, however, was to investigate tank-specific dependencies as well as conduct a dosimetric comparison between four distinct water scanning systems. Methods: Four water scanning systems were studied including the PTW MP3-M Phantom Tank, the Standard Imaging DoseView 3D, the IBA Blue Phanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although this is especially critical for profile acquisition, it also plays a role for reference PDI data acquisition. Saenz et al 36 . showed that the maximum PDI difference for a 6 MV 10×10$10\nobreakspace \times \nobreakspace 10$ cm 2 field between high‐speed (50 mm/s) and low‐speed (15 mm/s) scanning can be up to 0.8% at d max and beyond depending on water tank model.…”
Section: Pdi Determination To Obtain Beam Quality Specifiersmentioning
confidence: 99%
“…Although this is especially critical for profile acquisition, it also plays a role for reference PDI data acquisition. Saenz et al 36 . showed that the maximum PDI difference for a 6 MV 10×10$10\nobreakspace \times \nobreakspace 10$ cm 2 field between high‐speed (50 mm/s) and low‐speed (15 mm/s) scanning can be up to 0.8% at d max and beyond depending on water tank model.…”
Section: Pdi Determination To Obtain Beam Quality Specifiersmentioning
confidence: 99%